A broad overview comparing a fungal, thermal and acid pre-treatment of bean straw in terms of substrate and anaerobic digestion effect. (November 2020) - Montoya-Rosales, J.J.; Peces, M.; González-Rodríguez, L.M.; Alatriste-Mondragón, F.; Villa-Gómez, D.K.
Abstract: A comparison of lignocellulose degradation, energy requirements, biogas production and microbial community analysis was done between a fungal ( Pleurotus ostreatus, 28 d, 35 °C), thermal (1 h, 121 °C) and acid (2% HCl, 2 h, 123 °C) pre-treatment of bean straw. The results revealed that the type of pre-treatment had a great impact on lignocellulose degradation and energy demand, where the acid pre-treatment had higher solubilization capacity (lignin 67%, hemicellulose 68% and 0.49 g sugars·g −1 bean straw) and demanded less energy as compared with the fungal pre-treatment. Contrary, the type of pre-treatment did not have an apparent effect on the anaerobic digestion of the hydrolysates after 37 days of bioreactors operation in terms of biogas yield (142–165 mL g −1 chemical oxygen demand-COD), COD and sugars degradation (>80%). The bioreactor using acid pre-treatment hydrolysates showed differences in the total bacterial and archaea estimates, with a more pronounced increase in archaea ( Euryarchaeota ) and bacteria ( Bacteroidetes, Firmicutes, and Proteobacteria ), suggesting a more favorable composition for microbial growth. Overall, the acid pre-treatment was the most effective on all the parameters compared in this study. Further studies should include other important parameters to consider when selecting a pre-treatment method including environmental and economic implications of solid phase disposal and pH adjustment. Graphical abstract: Image 1 Highlights: Effect of a fungal, acid and thermal pre-treatment of bean straw were compared. Anaerobic digestion of hydrolysates from pre-treatments were also compared. Acid pre-treatment yielded higher sugar solubilization with less energy demand. Type of pre-treatment led to similar biogas yield but not microbial community. Increase of archaea/bacteria occurred in the bioreactor from the acid pre-treatment.